Safety, tolerability, pharmacokinetics, and pharmacodynamics of the novel γ‐secretase modulator, E2212, in healthy human subjects. (2nd January 2014) - Yu, Yanke; Logovinsky, Veronika; Schuck, Edgar; Kaplow, June; Chang, Min‐kun; Miyagawa, Takehiko; Wong, Nancy; Ferry, Jim
Abstract E2212, a novel γ‐secretase modulator, is under development for the treatment of Alzheimer's disease. The safety, tolerability, pharmacokinetics, and pharmacodynamics of single ascending oral doses (10–250 mg, double‐blind, placebo‐controlled, randomized) of E2212 were evaluated. In this phase I clinical trial, E2212 was found to be well tolerated in single doses. Maximum tolerated dose was not achieved up to 250 mg. Most AEs were mild to moderate in severity with no identifiable dose related pattern. There were no clinically significant findings on physical and ophthalmologic examinations as well as vital signs, laboratory, ECG and C‐SSRS assessments. E2212 was rapidly absorbed, with median tmax values ranging from 0.5 to 1.0 h. E2212 exhibited biphasic disposition with the terminal t1/2 of 12.5–19.0 h. Renal excretion was the minor pathway for E2212 elimination. Increased PD response (reduction in plasma concentrations of Aβ(x–42)) was observed with increasing doses. The maximum PD response was observed in the highest dose 250 mg cohort, with ΔAUAC(0–24 h) of 44.1% and Amax of 53.6%. These results support further clinical development of E2212.